Dimensi Ideologis Pendidikan Sejarah Islam pada Materi Sejarah Kebudayaan Islam di Madrasah Aliyah - Ahmad Yusuf Prasetiawan; Lisa'diyah Ma'rifataini (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2020)
The idea of eliminating war content in Islamic history is one response to the symptoms of religious attitudes, which tend to be exclusive. Religious attitudes correlate with a person's level of historical mastery, because history has a strategic function; in addition to providing information on the past, it can also construct emotions, allowing students to take sides to support or reject one of the parts. This study aims to see how the content of Islamic history education contains an ideological cleavage between modernist-traditionalists, which correlates with students' religious attitudes. Research using a descriptive qualitative approach through construction analysis methods and content analysis, namely, analysis models used to reveal, understand, and capture a text or discourse's message. The object being studied is the SKI material for class XII Madrasah Aliyah, as stipulated in the Decree of the Director-General of Islamic Education No. 2676 of 2013. This study's findings indicate that the class XII SKI material displays opposing ideological features between Modernist and Traditional Islam within Muslims' sociological structure in Indonesia. Students' religious attitudes have the potential to be dichotomous and affiliated in one part. Even though the object of the objective seems to content objective students' mastery of comprehensive, critical knowledge and has an objective comparative analysis. The effect of exclusivity can still occur if there is a shift in the substance of education from scientific objectivity to the hegemony of power.